2015
DOI: 10.1016/j.conbuildmat.2015.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-activated concrete: Engineering properties and stress–strain behavior

Abstract: h i g h l i g h t sThe engineering properties of alkali-activated concretes (AAC) are determined.Results are compared to existing models for portland cement concrete (PCC). Models are proposed to predict tensile strength and modulus of AAC. AAC exhibits higher tensile strength and lower Poisson's ratio than PCC. Alkali-activated slag concrete is much more brittle than PCC. a b s t r a c tThis paper presents an investigation into the tensile strength, modulus of elasticity, Poisson's ratio, and stress-strain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(83 citation statements)
references
References 31 publications
5
77
1
Order By: Relevance
“…Encouragingly, previous research [5][6][7][8][9] confirms that alkali-activated slag concrete (AASC) offers a range of performance benefits, such as high mechanical strength at early stages of curing, excellent acid-resistant characteristics, good resistance to freeze-thaw cycles and resistance to elevated temperatures. As such, the production and performance of AASC have been a highly active area of academic and industrial research over the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…Encouragingly, previous research [5][6][7][8][9] confirms that alkali-activated slag concrete (AASC) offers a range of performance benefits, such as high mechanical strength at early stages of curing, excellent acid-resistant characteristics, good resistance to freeze-thaw cycles and resistance to elevated temperatures. As such, the production and performance of AASC have been a highly active area of academic and industrial research over the past decades.…”
Section: Introductionmentioning
confidence: 99%
“…This supports the findings of other studies which also found lower tensile strengths for geopolymers compared to Portland cement. [28,29] Some studies however have suggested improved tensile strength compared to Portland cement. [30] The tensile strength of the specimens exposed to crude oil showed a steady value at the time intervals.…”
Section: Permeabilitymentioning
confidence: 97%
“…Analogous to current concrete standards, the mechanical properties of AACs can be expressed as a function of the compressive strength by means of empirical models. In the case of the flexural and/or tensile strength, initial results by the authors show that the 28‐day tensile strength of AACs exceeds the predictions given in EN 1992:2011, demonstrating an increased tensile resistance …”
Section: Performance Of Structural Concretes Based On Aabsmentioning
confidence: 99%